Short-time analysis of RC beams strengthened with or without FRP plates - Palomino Tamayo, Jorge Luis (2009)
The analytical model proposed by Bazant & Oh based on compatibility of deformations and equilibrium of forces in RC cross sections is extended and presented to predict short-time deformations. Stresses and deflections in beams strengthened with 01' without FRP plates epoxy- bonded to the tension face of rectangular and T cross sections. The theory assumes concrete to have a nonzero tensile carrying capacity. A parametric study was conducted to invesugate some design parameters such as plate area. plate stiffness and strength, concrete compressive strength and steel reinforcement ratio. To this end. moment-curvat ure diagrams lI'ere generated to know the influence of such parameters in the flexural response of the section. In all cases studied, adding the plate to the cross section increases the yield and ultimate tnoment capacity substantially in sections with a low steel reinforcenient ratio in tension being this increase more significant in doubly RC sections rather than in singly ones. Furthermore, results indicate that this increased flexural capacity could vary from 1.1 to 3.3 times the original strength of the section. Finally, the increase of concrete compressive strength does not increase the ultimate moment capacity significantly as it does when it is accompanied with the plate. Results show that the increased flexural capacity due to combined action could be as high as 4 times the original strength of the section.